Gerontology concept: Toward ego integrity through Taman Pendidikan Al-Quran (TPA) in order to second demographic bonus 2035 - AZKA KARIMA; DZIKRINA IZATUNIDA; UKHDA INDRI MARGA RISKA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: To prepare for the demographic windfall of 2035, this study seeks to understand how Taman Pendidikan Al-Qur’an (TPA) contributes to developing strong identities among the elderly. For the elderly, TPA is a tool for achieving ego integrity. Learning to recite the Quran while upholding Islamic principles is known as TPA.Methodology: This research, which employs qualitative methods such as interviews and observations, examines the experiences of three elderly female victims of the Mount Merapi eruption in Yogyakarta, which is currently being monitored by the TPA. As a result, we can state the following as our "findings:" The results show that TPA helped the elderly maintain their sense of self-worth. This study’s findings will help the elderly achieve TPA ego integrity. The elderly who can put aside their pride and contribute meaningfully to their communities will help the government reap the benefits of the demographic dividend.Novelty/Implications: The results are helpful because elderly people with strong senses of self-worth can contribute to government efforts to deal with the demographic dividend by helping to maintain economic stability and social cohesion in their communities.